The functionality of Sotho as a previously marginalised language in a multilingual educational setting. - Marupi, Omphile; Tshotsho, Baba Primrose; Nhongo, Raphael (Richtmann Publishing, 2022)
The language policy issues in Zimbabwe are embedded in three documents which are the Education Act of 1987, the Nziramasanga Commission, and the current constitution which was passed into law in 2013. The paper examines the negatives and positives of these policies in education and how they facilitate the inclusion and exclusion of Sotho. The vague policies which are evasive on how indigenous languages should be treated when it comes to their use as media of instruction are problematised. Data used in this paper was supplemented with information that came from interviews with eight teachers from schools in Gwanda. It is argued in this paper that the policies and pieces of legislation are not devoted to the equal advancement of indigenous languages. It is concluded that the functionality of Sotho in the education sector in Zimbabwe is mainly hindered by the government policies that do not recognise the co-existence of languages but rather create a linguistic war zone where they have to fight to dislodge one another. The paper advocates for the recognition of harmonious co-existence of languages in education where all the languages found in a geographical space are not restricted but are made to function equally and simultaneously.